Dysphagia in neurological disorders - Sofya A. Zaytsevskaya; Roman K. Lyukmanov; Elena S. Berdnikovich; Natalya A. Suponeva (Анналы клинической и экспериментальной неврологии)
Neurogenic dysphagia is a disorder with impaired swallowing, which is caused by various disorders of the central and peripheral nervous systems, neuromuscular transmission, or muscles. Dysphagia is one of the most common and at the same time the most dangerous symptoms of many neurological disorders. Patients with dysphagia often have severe disability, a higher risk of aspiration pneumonia, and significantly increased mortality rate. Despite the availability of many diagnostic screening methods, clinical scales, questionnaires, and instrumental diagnostic methods, the issue of neurogenic dysphagia is underestimated, especially in the early stages. As a result, patients do not receive timely treatment and prevention of dysphagia and associated complications. Validation of available diagnostic scales, development of international protocols and standards for the diagnosis, treatment, and prevention of dysphagia and associated complications are important to establish a unified and evidence-based approach for patients with dysphagia.